Design and Prototype of an Automatic Dam Monitoring and Control System. - Kiconco, Dalison (Kabale University, 2024)
Dams are one of the major water sources for irrigation, electricity generation, etc. in Uganda. Dams have played a vital role since the time of colonialism. The lack of a proper dam management system has been causing several losses including the recent floods. Inspired by the existing rural and socio-economic problems, an innovative and feasible automatic control system can be developed for dam management purposes. This paper also proposes a novel idea of collecting and sharing real-time information about water levels with the people living near its bank. A highly precise water level monitoring system and timely reports to the locality are also developed. When the water level crosses the threshold condition, alert messages will be sent to the people and the shutters will open automatically, retaining water to its normal level. Timely warnings to every person living in the locality and timely opening of shutters can thereby reduce the risks of loss of life and prevent disasters. Hence, automation of dam systems using Arduino, ultrasonic sensors, GSM modules, and motors, creates a new eye for both the Government as well as the people in the locality for creating mitigation plans.